Challenges and Prospects of Microporous Membranes for High‐Temperature Hydrogen Separation - Xiaoheng Jin; Xing Wu; Derrick Ng; Benny D. Freeman; Tao He; Zongli Xie (Small Structures)
The development of microporous membranes for high‐temperature hydrogen (H2) separation is crucial for advancing hydrogen as a clean energy source. This review critically evaluates recent progress in materials and technologies designed for H2 separation at elevated temperatures, focusing on the challenges and prospects of microporous H2 separation membranes derived from silica, zeolites, carbon molecular sieves, and metal–organic frameworks. Key challenges in membrane performance at elevated temperatures, including defect formation and hydrothermal stability, are examined. The review also explores advances in addressing significant engineering challenges, such as high‐temperature sealing and defect detection, which are essential for ensuring membrane performance and reliability. Additionally, this review explores future research directions aimed at enhancing membrane efficiency and advancing the industrial scalability of high‐temperature H2 separation technologies. This review provides insights into overcoming the materials and engineering hurdles that must be addressed to enable the next generation of high‐temperature H2 separation membranes.